2019
DOI: 10.5937/fizkul1902261k
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the complex training method on maximal isometric force production of junior basketball players

Abstract: During the period of ten weeks, a study has been conducted on the effects of a complex training method on the maximal isometric muscle force, its peaking time, and the rate of force development in the semi-squat test. The participants of the study were twenty junior basketball players (average age 16.4+/-0.7; mean body height 186.2cm+/-9.2; mean body weight 75,4+/-7.5kg; mean body fat percentage 12,83%+/-1.15). The participants were divided into experimental (n=10) and control group (n=10). The experimental gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As a result, 1,031 articles were excluded, and 25 articles were evaluated in full detail according to the inclusion and exclusion criteria through literature review and other screening processes. After the study selection process, although 11 articles (4,26,28,42–44,54,55,57,59,67) met the eligibility criteria (Figure 1) 2 articles (10,36) were excluded from this systematic review and meta-analysis because they did not meet the quality criteria. As a result, a meta-analysis was carried out with 11 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, 1,031 articles were excluded, and 25 articles were evaluated in full detail according to the inclusion and exclusion criteria through literature review and other screening processes. After the study selection process, although 11 articles (4,26,28,42–44,54,55,57,59,67) met the eligibility criteria (Figure 1) 2 articles (10,36) were excluded from this systematic review and meta-analysis because they did not meet the quality criteria. As a result, a meta-analysis was carried out with 11 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Different training methods contained traditional strength training and basketball training. Young male basketball players were 82% of the participants (4,26,28,42,43,54,55,59,67). Although one study was conducted with young female basketball players (57), the other study was performed with a mixed group of participants (44).…”
Section: Resultsmentioning
confidence: 99%
“…This reduces the error of the results and ensures the reliability of the experimental results. 10 We use the ternary phase diagram to analyze the angle distribution of the hip, knee, and ankle joints. The study found that 16 subjects had less variability in CMJ movements.…”
Section: Discussionmentioning
confidence: 99%